Giant Epidermal Inclusion Cyst of the Anterior Chest Wall - Jyoti, Sai; Gupta, Prajwala (Annals of Pathology and Laboratory Medicine, 2025)
Epidermal inclusion cysts (EICs) are benign cutaneous lesions resulting from the implantation and proliferation of epidermal elements within the dermis. Although commonly observed in areas rich in hair follicles such as the scalp, neck, and trunk, giant variants (≥5 cm) are rare. EICs located over the anterior chest wall are exceedingly uncommon, with only isolated case reports in literature. We present a case of a 38-year-old male with a longstanding giant cystic swelling on the anterior chest wall. Fine needle aspiration cytology (FNAC) revealed classic features of an EIC, thereby assisting in an accurate preoperative diagnosis. This report emphasizes the relevance of cytological evaluation in identifying large benign lesions in unusual locations.